The Role Of Financial Literacy, Access To Capital, And Entrepreneurial Orientation On MSMEs Business Performance - Mayndarto, Eko Cahyo (Journal Management & Economics Review (JUMPER), 2025)
This study explores the impact of financial literacy, access to capital, and entrepreneurial orientation on the business performance of Micro, Small, and Medium Enterprises (MSMEs). MSMEs play a vital role in economic development, yet they often face significant challenges related to financial management, funding, and strategic direction. Using a quantitative approach, data were collected from 150 MSME owners through structured questionnaires and analyzed using multiple linear regression. The results reveal that financial literacy, access to capital, and entrepreneurial orientation all have significant and positive effects on business performance. Among these, entrepreneurial orientation exerts the greatest influence, highlighting the importance of innovativeness, proactiveness, and risk-taking in enhancing firm outcomes. The model explains 54.7% of the variance in MSME performance, suggesting a strong predictive relationship. The findings provide valuable insights for stakeholders, including policymakers, financial institutions, and entrepreneurship educators, aiming to strengthen the resilience and growth of MSMEs through improved financial capability, easier access to funding, and the cultivation of entrepreneurial mindsets.